(3OQGSI aj GdCfJQhHhdhLjG GdEbJUGOjIs - (3eMeO jSQj GHQGgje(B, (3OYHSs ((3GdEScfOQjI(B:s (3OGQ GdeYGQa(B,s, 1996)
(3CfeGW GdJHGOd aj GdeLJeY GdHOhj(B- (3GdCfeGW GdESJgdGcjI hGdEONGQjI aj GdeLJeY GdHOhj(B- (3GdJQGce hGdEgOGQ ddWGbI hddehGO aj GdeLJeY GdHOhjs
Keywords: (3GdEONGQs; (3GdJHGOds; (3Yde GdGLJeGY GdGbJUGOj, GdJLGQIs